1999
DOI: 10.1002/(sici)1098-2744(199901)24:1<36::aid-mc6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of G1 cell-cycle protein expression and induction of p53 but not p21/waf1 by the DNA-modifying carcinogen 2-acetylaminofluorene in growth-stimulated hepatocytes in vitro

Abstract: 2-Acetylaminofluorene (AAF) is a potent tumor promoter in rat liver carcinogenesis models. In the resistant hepatocyte model, AAF is combined with a growth stimulus for efficient promotion of preneoplastic lesions. The promoting property of AAF in this model is closely associated with mito-inhibition of normal hepatocytes, an effect to which initiated cells are resistant. How AAF induces growth arrest is not known, but genotoxic as well as non-genotoxic effects have been implicated. To elucidate the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Preneoplastic lesions, as a result of altered xenobiotic metabolism, appear to be protected from this mitoinhibitory effect [8]. In a previous study, we found that mitoinhibition of AAF-exposed cultured hepatocytes was associated with increased p53 protein expression and reduced pRb hyperphosphorylation but not with p21/CIP1 induction [6]. Also, during in vivo regeneration of AAF-exposed rat liver, the binding of p21/CIP1 to cyclin E or cdk2 was not increased, although cdk2 complex formation and activation were inhibited.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Preneoplastic lesions, as a result of altered xenobiotic metabolism, appear to be protected from this mitoinhibitory effect [8]. In a previous study, we found that mitoinhibition of AAF-exposed cultured hepatocytes was associated with increased p53 protein expression and reduced pRb hyperphosphorylation but not with p21/CIP1 induction [6]. Also, during in vivo regeneration of AAF-exposed rat liver, the binding of p21/CIP1 to cyclin E or cdk2 was not increased, although cdk2 complex formation and activation were inhibited.…”
Section: Discussionmentioning
confidence: 79%
“…A sustained ERK activation is required for the induction of cyclin D1, one of the ®rst events of cell-cycle progression [19]. Indeed, our previous studies have demonstrated that mitoinhibition of AAF-exposed primary hepatocytes is associated with a profound inhibition of cyclin D1 induction [6]. Thus, the demonstrated effects of AAF on ERK functions may have severe effects on G 1 progression, contributing to the mitoinhibitory effects of this carcinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both CDK4 and 6 are important for cell cycle regulation, specifically G 1 phase progression, with their activity strictly restricted to the G 1 -S phase [35]. Mutations in these genes have been found to be significantly associated with tumorigenesis of several cancers [6, 7].…”
Section: Introductionmentioning
confidence: 99%